PENGARUH STRATEGI PEMASARAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA WARUNG BAKSO “IBU CICIH” DI DESA LANGENSARI KECAMATAN SOLOKANJERUK KABUPATEN BANDUNG - Isan Handiyana; Ani Surtiani (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study aims to analyze the effect of marketing strategy and product quality on consumer purchasing decisions at “Ibu Cicih” Bakso Stall located in Langensari Village, Solokanjeruk Subdistrict, Bandung Regency. The increasingly intense competition in the culinary business sector requires micro, small, and medium enterprises (MSMEs) to implement appropriate marketing strategies and maintain product quality in order to attract and retain consumers. The marketing strategy examined in this study includes the marketing mix, consisting of product, price, place, and promotion, while product quality is assessed based on taste, texture, hygiene, consistency, and the suitability of portion size with price. Consumer purchasing decisions are viewed as the result of a consumer consideration process in selecting and purchasing products. The research method used is a quantitative method with descriptive and verificative approaches. Data were collected through the distribution of questionnaires to consumers of “Ibu Cicih” Bakso Stall as research respondents. Data analysis techniques include descriptive analysis, correlation testing, coefficient of determination, and partial and simultaneous hypothesis testing to determine the relationships and effects among variables. The results of the study indicate that marketing strategy has a positive and significant effect on consumer purchasing decisions. Product quality is also proven to have a positive and significant effect on purchasing decisions. Simultaneously, marketing strategy and product quality have a significant effect on consumer purchasing decisions. This indicates that the implementation of effective marketing strategies and consistent improvement of product quality can enhance consumer purchasing decisions. This study is expected to provide practical contributions for MSME actors, particularly in the culinary sector, as a consideration in formulating more optimal marketing strategies and maintaining product quality to improve business competitiveness and sustainability.